Screening of polymerization effect with Alginate-HPMC-Guar gum on Polymer-Based Interpenetrating Networks in Sodium Alginate Raft System for Sustained Drug Delivery - Sanchita Mandal (International Journal of Pharmaceutical & Biological Archive, 2025)
Background: Various technologies have been developed recently, including creating controlled drug delivery systems to address several physiological challenges and gastric retention and emptying time. To combat this issue, new methods of medication delivery have been created. A recently developed technique called the raft-forming system can overcome several obstacles in the gastroretentive drug delivery system. Materials and Methods: This study was supervised to assess the effects of polymers like sodium alginate (SA), guar gum (GG), and hydroxypropyl methylcellulose (HPMC) and their grades in the formation of the raft. It showed the feasibility of prolonging the residence time in the stomach and the release rate of metronidazole, which was used here as a model drug. Four different HPMC grades were used (HPMC K100 M, HPMC K40 M, HPMC K15 M, and HPMC K4 M) with SA and calcium carbonate acting as divalent cation salt. The formed rafts were characterized by physical appearance, pH, in vitro gelling capacity, in vitro buoyancy study, shear stress by viscosity measurement, the density of raft, in vitro floating ability, raft volume, raft thickness, raft resilience, % swelling index, and Fourier transform infrared spectroscopy. Results: This formulation had no distinct difference in physical appearance, but HPMC 100 showed a deeper color than other formulations. pH ranged from 2 to 3, with HPMC 100 having the highest pH of 3. In situ, gelling capacity of HPMC 100 showed the lowest time of 5 s, and buoyancy capacity and resilience timing were the same for all more than 24 h and 4 h, respectively. Conclusion: The rest of the characterization of raft containing SA and HPMC 100 formulation takes the highest position. Based on the screening study, HPMC 100 demonstrated superior performance to other polymers and has been selected for further investigation.